Genome-wide identification and expression analysis of the HAK/KUP/KT gene family in Moso bamboo - Guo, Hui; Tan, Jiaqi; Jiao, Yang; Huang, Bing; Ma, Ruifang; Ramakrishnan, Muthusamy; Qi, Guoning; Zhang, Zhijun (Frontiers in Plant Science, 2024)
The K + uptake permease/high-affinity K + /K + transporter (KUP/HAK/KT) family is the most prominent group of potassium (K + ) transporters, playing a key role in K + uptake, transport, plant growth and development, and stress tolerance. However, the presence and functions of the KUP/HAK/KT family in Moso bamboo.(Phyllostachys edulis (Carriere) J. Houzeau), the fastest-growing plant, have not been studied. In this study, we identified 41 KUP/HAK/KT genes (PeHAKs) distributed across 18 chromosomal scaffolds of the Moso bamboo genome. PeHAK is a typical membrane protein with a conserved structural domain and motifs. Phylogenetic tree analysis classified PeHAKs into four distinct clusters, while collinearity analysis revealed gene duplications resulting from purifying selection, including both tandem and segmental duplications. Enrichment analysis of promoter cis-acting elements suggested their plausible role in abiotic stress response and hormone induction.Transcriptomic data and STEM analyses indicated that PeHAKs were involved in tissue and organ development, rapid growth, and responded to different abiotic stress conditions. Subcellular localization analysis demonstrated that PeHAKs are predominantly expressed at the cell membrane. In-situ PCR experiments confirmed that PeHAK was mainly expressed in the lateral root primordia. Furthermore, the involvement of PeHAKs in potassium ion transport was confirmed by studying the potassium ion transport properties of a yeast mutant. Additionally, through homology modeling, we revealed the structural properties of HAK as a transmembrane protein associated with potassium ion transport. This research provides a solid basis for understanding the classification, characterization, and functional analysis of the PeHAK family in Moso bamboo.